Electrochemical biosensor based on silicon nanowires/ platinum nanoparticles associated with loop-mediated isothermal amplification for detection of porcine DNA in food - Kusnin, Norzila (2024)
In the past, issues with food adulteration, such as lard adulteration and the use of pig intestine casing sausage, have been the major issues in Malaysia since they are related to the halal status of the food products. The porcine derivatives include pork fat (lard), porcine gelatin, porcine blood plasma and mechanically recovered meat usually used by the food manufacturers in most countries because of their cheaper price and ready availability. Hence in order to ensure the food and dairy products that are free from the porcine derivatives, there is a requirement of developing sensitive and rapid methods which can trace even the minute composition. In this work, an electrochemical DNA biosensor has been developed based on the fabrication of silicon nanowires/platinum nanoparticles (SiNWs/PtNPs) onto a screen-printed carbon electrode (SPCE) for the detection of Sus scrofa mitochondrian DNA (mtDNA) in food utilizing ferrocenylnaphthalene diimide (FND) as indicator. In this study, the morphology and elemental analysis of SiNWs/PtNPs-modified SPCE was analyzed by field emission scanning electron microscopy (FESEM) combined with energy dispersive X-ray (EDX), respectively. The cyclic voltammetry (CV) was used to study an electrical contact between the PtNPs and the screen-printed working electrode through SiNWs, while electrochemical impedance spectroscopy (EIS) was used to measure the charge transfer resistance of the modified electrode. Based on the results, it clearly showed that the SiNWs/PtNPs was successfully coated onto the electrode and the effective surface area for SiNWs/PtNPs-modified SPCE was increased 16.8 times as compared with the bare SPCE. The differential pulse voltammetry (DPV) used for the detection of porcine DNA with FND as an intercalator was confirmed for its specific binding to the double-stranded DNA (dsDNA) sequences. The increase of FND peak current was obtained after hybridization detection by fabricated electrode. The optimal performance of SiNWs/PtNPs-modified SPCE for electrochemical detection of porcine DNA was optimize with several parameters; DNA probe concentration (5 μM), immobilization time (24 hours), pH buffer (7.5), different types of salts in the hybridization buffer (NaCl), salt concentration (1.0 M), hybridization temperature (40 °C) and incubation time (20 min), respectively. The developed biosensor showed selective response towards complementary target DNA and able to distinguish noncomplementary and mismatched DNA oligonucleotides. The SiNWs/PtNPs-modified SPCE that was fortified with DNA hybridization demonstrated a good linearity in the range of 0.0219 ng/μL to 219 ng/μL (R2 = 0.96) with the detection limit of 175.2 ng/μL. The developed DNA sensor also showed excellent current reproducibility with a relative standard deviation (RSD) of 2.52% when testing with a series of five modified electrodes under the same preparation batch. The sensor demonstrated good storage stability with slight attenuation from the initial current (week 1) after week 5 of storage. In order to assess the capability of the developed DNA biosensor to reliably detect real samples, the application of a suitable amplification method was considered. Loop-mediated isothermal amplification (LAMP) was chosen due to the rapid amplification time and isothermal conditions, which simplify the equipment requirements. The preparation of a specific and amplified target gene using LAMP was investigated. A set of specific primers (F3, B3, FIP, BIP, and LF) were successfully designed to initiate strand displacement and DNA synthesis under isothermal conditions. The amplification parameters, including temperature and incubation time, were optimized, with positive results detected at a stable temperature of 63°C for 60 minutes. The results were visualized through the turbidity caused by the white precipitate of magnesium pyrophosphate, a byproduct of the amplification process. Cross-reactivity studies with various types of meat and processed foods demonstrated good reliability, specifically for detecting porcine species. In conclusion, the DNA biosensor was successfully developed and can be used to detect specific target of porcine DNA in food for halal purposes. This biosensor demonstrates high specificity, making it a valuable tool for ensuring the authenticity of halal-certified products. Its application in the food industry can significantly enhance quality control measures, thus providing consumers with greater confidence in the halal status of their food.